Fungsi dan Relevansi Filsafat Hukum bagi Rasa Keadilan dalam Hukum Positif - R. Arry Mth. Soekowathy (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
The writer in this paper tried to onvestigate and describe the philosophical thoughts of the function of Law Philosophy and its relevance to the sense of justice according to the positive law. The formulated hypothesis are (1) The enfoercement of the law materialized the justice and the certainty and insurance in justice (2) The description of the sense of justice should be in the existing positive law (3) The philosophy of law represented the search for the deepest meaning of the ultimate result in the law wisdom